'Don't be the same, be better': an exploratory study on police mobile technology resistance. (15th January 2021) - Abbas, Noorhan; Policek, Nicoletta
ABSTRACT: Purpose : This contribution stems from the acknowledgment that the post-adoptive officers' behaviour and utilisation of the mobile technology has not yet been examined. Between 2008 – 2010, the Home Office funded the Mobile Information Programme to increase the visibility of police officers and increase the efficiency and effectiveness of the Police Service. This programme had enabled the roll-out of 41, 000 mobile devices to police officers, allowing them to spend a greater percentage of their working time out of police stations. Yet, in 2012, the NPIA's evaluation of the increase in police officers' visibility showed that on average, officers spent around 18 minutes extra per shift out of the station using mobile devices. Methodology : To overcome the paucity of available data, a pilot study adopting a multi-method approach was conducted in a medium-sized constabulary in the UK. Data collection methods included focus groups, Q cards methodology and an online survey. Findings : This study sheds light on officers' main reasons for post-adoptive resistance to using the mobile devices and its impact on the quality of police data recorded. Furthermore, it delineates innovative ways of enhancing police mobile technology training to boost technology adoption in police forces.